The effect of eight weeks of 30-20-10 interval training on serum spexin levels and lipid profile in obese middle-aged men - Hamid Yazdanshenas; Roghayeh Fakhrpour; Bahloul Ghorbanian (Shahid Beheshti University, 2023)
Background and Purpose: The purpose of this study was to investigate the effect of 30-20-10 interval training on the serum spexin level and lipid profile of obese men in order to measure the effect of physical activity on increasing spexin and improving lipid profile in obese men.Materials and Methods: Statistical population of Yezhohesh, 21 obese men (mean age 43.52±9.06 years, weight 108.11±16.42 kg, body mass index 35.42±7.14 kg/m2) who voluntary participated in the present study and were randomly divided into training (11 people) and control (10 people) groups. Training were performed for eight weeks and three sessions per week with the 30-20-10 exercise protocol, including interval training with approximately intensities of 30 seconds with 30%, 20 seconds with 60% and 10 seconds with 90-100% of maximum heart rate. These one-minute training were repeated five times (five minutes) and after 5 repetitions, they rested for two minutes and started the next five repetitions again, and it was repeated in three-four times of running. At the end of the intervention, serum spexin and lipid profile were measured by ELISA method. Within-group changes were analyzed using the dependent t-test. ANCOVA test was used in the data analysis in the pre-test-post-test design with the control group. where pre-test scores were used as covariate. Statistical analyzes were performed at the statistical level of P ≤ 0.05.Results: By examining the research results, it was found that 10-20-30 interval training caused a significant increase in the amount of spexin in the training group compared to the control group (P=0.010). Also, interval training 10-20-30 causes a significant decrease in the amount of TG variables (P=0.001), LDL-C (P=0.001), cholesterol (P=0.001) and a significant increase in HDL-C. (P=0.001) has been Based on the results, it was found that there is a significant relationship between cholesterol and changes in the serum levels of spexin in obese middle-aged men (P=0.004). Also, there is a significant relationship between changes in serum levels of spexin and changes in some anthropometric indices such as body mass index (P=0.05) and ratio of waist circumference to hip circumference (P=0.005) of obese middle-aged men.Conclusion: According to the results of the research, a significant increase in serum spexin and HDL-C and a significant decrease in cholesterol, triglyceride and LDL-C, it can be concluded that eight weeks of 30-20-10 interval training has an effect on the levels of the factors mentioned in obese middle-aged men. It can probably increase the serum levels of spexin and improve the lipid profile in these people.